Study of Chemical Characteristics of The Lambidaro River for Sustainable Environment - Hisni Rahmi; Restu Juniah; Azhar Kholiq Affandi (Indonesian Journal of Environmental Management and Sustainability, 2017)
Residents who live along the Lambidaro watershed, generally use river water to meet their daily needs such as bathing, washing and latrines. Around of Lambidaro is a residential and industrial group such as rubber industry, workshop, home industry, and mining. The activities contained along the watershed can lead to an increase in river water pollution load which can be seen from chemical characteristics. Increased pollution loads can cause the river environment to be unsustainable for the community. Sustainable environment means that the environment as a provider of resources for human life is able to maintain its carrying capacity. The purpose of study is to determine the chemical characteristics of river due to sand mining activities for the environment sustainable. This research is using pollution index method with parameter of chemical characteristics measured that is pH, DO, COD, BOD5, Fe, Mn, NH4, Nitrate, and Nitrite. The results of analysis of water chemical characteristics of the river indicate that the part close to estuary of the river is in good condition indicating that the location is environmentally sustainable. Meanwhile, the upstream to the middle river body is in mild contamination condition which means that the river environment has been contaminated.